KRAS inhibitors: going noncovalent - Matthias Drosten; Mariano Barbacid (Molecular Oncology, 2022)
KRASG12D is the most frequent KRAS mutation in human cancer with particularly high frequencies in pancreatic and colorectal cancer. Informed by the structure of the KRASG12C inhibitor adagrasib, Hallin et al. have now, through multiple rounds of structure‐based drug design, identified and validated a potent, selective, and noncovalent KRASG12D inhibitor, MRTX1133. This study demonstrated that MRTX1133 inhibited both the inactive and active state of KRASG12D and showed potent antitumor activity in several preclinical models of pancreatic and colorectal cancer, especially when combined with cetuximab, a monoclonal antibody against the EGFR, or BYL‐719, a potent PI3Kα inhibitor.